Ecological sustainability: reinvigorate and emulate African principles of life or cease to exist? - Mukoni, Manuku (Asian Economic and Social Society, 2017)
A publication by Mrs Manuku Mukoni a Lecturer in the Department of Gender Studies, Midlands State University, Zimbabwe